Hardiness as a Shield: A Moderated Mediation Model of Turnover Intention among Auditors - Gim, G.C.W.; Ooi, S.K.; Ramayah, T.; Lew, Tek Yew; Ting, Qian Hui (2023)
Auditors are associated with high workload, leading to increased turnover rates. Despite extant research on job stressors and coping strategies, the role of hardiness in mitigating these negative effects remains underexplored. Based on a moderated mediation model grounded on the conservation of resources (COR) theory, this paper aims to investigate the role of hardiness in reducing the impact of role overload and turnover among auditors. Based on the data gathered from 211 auditors and analysed using partial least squares structural equation modeling and PROCESS macro, the findings revealed that the positive relationship between role overload and turnover intention together with the mediation effect of role overload were weakened among auditors who had high level of hardiness. The research offers theoretical and practical implications by extending the conceptualisation and measurement of hardiness as a higher-order construct, enriching COR theory in the auditing context, and emphasising the contingent role of hardiness in mitigating the negative effects of role overload and turnover among auditors.